2011
DOI: 10.4137/cmo.s6927
|View full text |Cite
|
Sign up to set email alerts
|

The Role of T Lymphocytes in Cancer Patients Undergoing Immunotherapy with Autologous Dendritic Cells

Abstract: Introduction:Cancer stems from mutations in specific genes that induce uncontrolled cell proliferation. Dendritic cells (DCs) are important immunologic cells and play a crucial role in the induction of an antitumour response.Patients and methods:We examined the immune response mediated by T lymphocytes, helper T cells, cytotoxic T cells, and regulatory T cells, as well as the cytokines [interleukin (IL)-2, IL-12, interferon (IFN)-γ, tumour necrosis factor (TNF)-α and IL-10], produced by these cell populations,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…A study performed by our group contains a description of cancer patients who expressed IL-12 in CD4 + T lymphocytes 21. We did not find any similar findings in our literature review.…”
Section: Introductionsupporting
confidence: 46%
“…A study performed by our group contains a description of cancer patients who expressed IL-12 in CD4 + T lymphocytes 21. We did not find any similar findings in our literature review.…”
Section: Introductionsupporting
confidence: 46%
“…IL-12 represents a multifunctional cytokine that promotes a link between innate and adaptive immunity, by regulating the immune response, inducing the differentiation of CD4 + T cells into Th1 cells, and promoting the reactivation and survival of memory CD4 + T cells. IL-12 is described to be produced by antigen presenting cells (APCs), however our group has evidences that in certain situations, such as tumors, CD4+ lymphocytes could synthesize this cytokine [24]. Of course being an analysis of biopsies in this study can be analyzed IL-12 produced by both APCS and CD4+ T cells But the important thing is we found that this cytokine, as important in the development of cellular immunity, is reduced in the tumoral microenvironment according to lesion progression.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have focused on the development of immunotherapies with DCs using new differentiation and maturation protocols for the induction of an effective antitumor immune response (23,24).…”
Section: Monocyte-derived Dendritic Cells From Patients With Cervicalmentioning
confidence: 99%